(untitled) (Current Problems in Rail Vehicles, 2021)
CZ LOKO, a.s. expands its portfolio with hybrid and dual vehicles. By hybrid vehicle we mean a vehicle with a primarily battery source of traction energy with a backup unit – for example HybridShunter 400 and 1000. The dual vehicle then obtains energy from the overhead line (in dependent traction) or from a motor generator or traction battery (independent traction) – DualShunter 2000 DC and AC.